2019
DOI: 10.3389/fphar.2019.00088
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Norbinaltorphimine Produces Cumulative Kappa Opioid Receptor Inactivation

Abstract: Kappa receptor activation by dynorphins contributes to the anxiogenic, dysphoric, and cognitive disrupting effects of repeated stress, suggesting that kappa receptor antagonists might have therapeutic utility in the treatment of stress disorders. Three classes of kappa antagonists have been distinguished: non-selective, selective-competitive (readily reversible), and non-competitive (receptor-inactivating); however, which would be the most effective medication has not been established. To assess the utility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…However, the intriguing pharmacodynamic and pharmacokinetic properties of these compounds (which can include slow onset, slow emergence of selectivity, and extremely long duration of action) can complicate the design and interpretation of in vivo studies (Endoh et al, 1992;Broadbear et al, 1994;Ko et al, 2003;Melief et al, 2011). It has been suggested that these longer-acting k-antagonists are "receptor-inactivating agents" that may function at least in part by producing complex downstream functional changes (Chavkin et al, 2019). Several groups have developed shorter-acting selective k-antagonists, with more "canonical" pharmacodynamics and pharmacokinetics, and classic competitive properties (Grimwood et al, 2011;Peters et al, 2011;Rorick-Kehn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the intriguing pharmacodynamic and pharmacokinetic properties of these compounds (which can include slow onset, slow emergence of selectivity, and extremely long duration of action) can complicate the design and interpretation of in vivo studies (Endoh et al, 1992;Broadbear et al, 1994;Ko et al, 2003;Melief et al, 2011). It has been suggested that these longer-acting k-antagonists are "receptor-inactivating agents" that may function at least in part by producing complex downstream functional changes (Chavkin et al, 2019). Several groups have developed shorter-acting selective k-antagonists, with more "canonical" pharmacodynamics and pharmacokinetics, and classic competitive properties (Grimwood et al, 2011;Peters et al, 2011;Rorick-Kehn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This potentially safer low-dosing strategy was previously demonstrated to be effective in males (Chavkin et al, 2019).…”
Section: Duration Of Antinociceptive Action Of Norbni In the Tail-witmentioning
confidence: 96%
“…The release of endogenous opioid dynorphin peptides throughout the brain contributes to these adverse behavioral effects (Ehrich et al, 2015;Abraham et al, 2018a). For this reason, researchers have explored using kappa opioid antagonists as antidepressants and anti-addiction therapeutics in both pre-clinical research and human clinical trials (Buda et al, 2015;Carrol & Carlezon, 2013;Lowe et al, 2014;Chavkin et al, 2019). Three different forms of KOR antagonists have been identified: nonselective (e.g.…”
Section: Mol# 124 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antagonist-receptor complex formation happens by binding the small molecule to the active site or to the allosteric site on the receptor. Depending on the longevity of the antagonist-receptor complex, the activity of the antagonist compounds may be reversible or irreversible [3]. One main group of the receptors into the human cells is the opioid receptors (OR).…”
Section: Introductionmentioning
confidence: 99%